2021
DOI: 10.3390/diagnostics11122276
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Magnetic Resonance Imaging as a Diagnostic Aid for Hypermobile Lateral Meniscus

Abstract: Background: Hypermobile lateral meniscus is difficult to diagnose with imaging due to its absence of tears or anomalies. We aimed to clarify the accuracy of the preoperative diagnosis using magnetic resonance imaging (MRI). Methods: The preoperative MRI status of the posterosuperior popliteomeniscal fascicle (sPMF), anteroinferior popliteomeniscal fascicle (iPMF), and popliteal hiatus were examined retrospectively on sagittal images in the hypermobile lateral meniscus group (n = 22) and an age- and gender-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…investigated the diagnostic accuracy of MRI for isolated hypermobile lateral meniscus. 16 With a cohort of 66 patients—22 HLM patients matched 2:1 to controls—researchers demonstrated that upon MRI assessment of the integrity of the sPMF, iPMF, and popliteal hiatus in each knee by 2 blinded orthopedic surgeons, there was a statistically significant odds ratio for a diagnosis of HLM in the setting of worse preoperative MRI findings within each structure (sPMF OR 5.50 [ P = .036]; iPMF 12.20 [ P = . 002]; popliteal hiatus 5.00 [ P = .034]).…”
Section: Discussionmentioning
confidence: 99%
“…investigated the diagnostic accuracy of MRI for isolated hypermobile lateral meniscus. 16 With a cohort of 66 patients—22 HLM patients matched 2:1 to controls—researchers demonstrated that upon MRI assessment of the integrity of the sPMF, iPMF, and popliteal hiatus in each knee by 2 blinded orthopedic surgeons, there was a statistically significant odds ratio for a diagnosis of HLM in the setting of worse preoperative MRI findings within each structure (sPMF OR 5.50 [ P = .036]; iPMF 12.20 [ P = . 002]; popliteal hiatus 5.00 [ P = .034]).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital or traumatic insufficiencies of the PMF are highlighted as a common cause of HLM [52]. The PMF are posterolateral meniscocapsular extensions that proceed inferiorly from the external edge of the LM to the popliteus musculotendinous complex, asserting a significant impact on rotational stability of the knee and restricting anterior displacement of the posterolateral portion of the LM [16,36,47,48].…”
Section: Introductionmentioning
confidence: 99%